Combined agro-ecological strategies for adaptation of organic horticultural systems to climate change in Mediterranean environment - Diacono, Mariangela; Fiore, Angelo; Farina, Roberta; Canali, Stefano; Di Bene, Claudia; Testani, Elena; Montemurro, Francesco (Italian Journal of Agronomy, 2016)
Agricultural biodiversity and related agro-ecological measures could play a crucial role in the agro-ecosystems adaptation to climate changes, thus sustaining crop production. The objective of this study was to assess the suitability (and the best combination) of agro-ecological techniques as potential resilience strategies in organic horticultural systems in a Mediterranean environment. A long-term experimental device called MITIORG (Long-term climatic change adaptation in organic farming: synergistic combination of hydraulic arrangement, crop rotations, agro-ecological service crops and agronomic techniques) is set-up at Metaponto (MT), testing the following agro-ecological measures as well as organic and conservation farming best practices: i) hydraulic arrangement by a kind of ridge-furrow system; ii) cash crop rotations; iii) agro-ecological service crops (ASC) introduction; iv) ASC termination techniques (green manure vs roller crimper); and v) organic fertilisation. The research here reported was carried out during the 2014-2015 season in the MITIORG device, on a rotation of cauliflower (Brassica oleracea L.) and tomato (Solanum lycopersicum L.) crops. A detailed description of the scientific cognitive process that led to setup of the device, its components explanation, as well as preliminary yield results are reported. The outcomes suggest that organic vegetable cropping systems, designed following agro-ecological principles, are able to sustain yield of cash crops in rotation, in spite of changes in temperature and rainfall of the study site. Experimental data available in the next years will allow a deeper integrated analysis of the manifold effects of agro-ecological measures on horticultural systems.